Indonesian EFL teachers’ content conceptualization and course organization: A portray of text-based teaching - Triastuti, Anita; Riazi, Mehdi (Universitas Pendidikan Indonesia, 2020)
Frequent changes of Indonesian English as a Foreign Language (EFL) national curriculum have transformed EFL teachers’ role from that of serving merely as curriculum transmitters into curriculum adapters. Accordingly, this study intended to explore how a group of Indonesian EFL teachers conceptualize content and course organization as guided by the Indonesian national EFL curriculum. A qualitative multiple-case study (Miles, Huberman, Saldana, 2014; Stake, 2006; Yin, 2014) was employed to collect and analyze data. Purposive within- and cross-case sampling techniques were used to select six EFL teachers; three experienced and three inexperienced teachers of public junior high schools in the Special Territory of Yogyakarta, Indonesia. Sources of data included instructional curriculum design assessments and pre-lesson semi-structured interviews. Analysis of the data revealed these teachers’ content conceptualization focuses on blending texts and English language skills that characterize the implementation of text-based teaching in the Indonesian EFL context. Results of the data analysis for course organization showed teachers’ insufficient understanding of the selected organizing principles for teaching texts. Such understanding led to inconsistency between theory and practice. The findings of the study shed light on a misconception about implementing text-based teaching. Implications of the study address the need to equip Indonesian EFL teachers with both the conceptual and practical knowledge of implementing the methodology of text-based teaching.